PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP SIKAP PEGAWAI MENGENAI PERUBAHAN DI BALAI DIKLAT INDUSTRI KEMENTERIAN PERINDUSTRIAN REPUBLIK INDONESIA - Hamid, Fajar; Sudibya, I Gde Adnyana; Rahyuda, Agoes Ganesha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
This study aims to analyze the effect job satisfaction and organizational commitment on attitude towards organizational change and the influence of commitment organizational mediation. Population in this study is Industry Training Centers’ employees from seven cities in Indonesia. This study used questionnaire as a research instrument and Partial Least Square (PLS) as a data analyze technic. The result shows that job satisfaction, has positive and significant effect on attitude towards organizational change, normative commitment, affective commitment,  and continuance commitment. Whereas, affective commitment and normative commitment have positive and significant effect on attitude toward organizational change. Moreover, continuance commitment has negative effect yet it’s not significant to attitude towards organizational change. Mediation test shows normative commitment and affective commitment influence partial mediation in accordance with job satisfaction to attitude towards organizational change.
Keywords: Job Satisfaction, Attitude Towards Organizational Change, Normative Commitment, Affective Commitment, Continuance Commitment